2021
DOI: 10.3390/ani11113236
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus membranaceus Alters Rumen Bacteria to Enhance Fiber Digestion, Improves Antioxidant Capacity and Immunity Indices of Small Intestinal Mucosa, and Enhances Liver Metabolites for Energy Synthesis in Tibetan Sheep

Abstract: Natural, non-toxic feed additives can potentially replace chemical medications and antibiotics that are offered sheep to improve performance. In the present study, Tibetan sheep were supplemented with the root of Astragalus membranaceus (AMT), a traditional herb used widely in China. Twenty-four male Tibetan sheep (31 ± 1.4 kg; 9-month-old) were assigned randomly to one of four levels of supplementary AMT: 0 g/kg (A0), 20 g/kg (A20), 50 g/kg (A50) and 80 g/kg (A80) dry matter intake (DMI). The A50 and A80 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Preceding in vivo studies have demonstrated a uniform increase in the proportion of Firmicutes by feeding AMR or a related substrate [7,24], as was determined in the current study. Regarding proportional changes in Bacteroidota, which increased in another assessment [25], only one group belonging to Bacteroidota (Muribacteria) changed with a significant decrease.…”
Section: Discussionsupporting
confidence: 73%
“…Preceding in vivo studies have demonstrated a uniform increase in the proportion of Firmicutes by feeding AMR or a related substrate [7,24], as was determined in the current study. Regarding proportional changes in Bacteroidota, which increased in another assessment [25], only one group belonging to Bacteroidota (Muribacteria) changed with a significant decrease.…”
Section: Discussionsupporting
confidence: 73%
“…To isolate the gut tissue, approximately 3 cm segments of the midpoint of the duodenum, jejunum, and ileum were collected and stored at −80 °C for gene expression analysis. The mucosal samples were collected by the method described by Wang et al [ 24 ]. Mucosal samples were stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples collected on d 60 were used for metabolome analysis. The preparation of the sample and analysis followed Wang et al (2021) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%